Social production and reproduction at the interface of public and private spheres - Segal, Marcia Texler, 1940-; Chow, Esther Ngan-ling, 1943-; Demos, Vasilikie P. (Advances in gender research ;, 2012)
This volume focuses on the gendered interfaces of the public and private spheres of life. In the 21st century these are no longer separate as women and men move from one to the other in the course of their daily lives and their life spans. The chapters examine the ways individuals, families and societies strive to balance paid and unpaid labor, engage in parenting and accomplish other care-work, seek education for themselves and their children, and respond to the mass media, sometimes under conditions of poverty or violence and often across international boundaries. These are the ways social life is produced and reproduced, protested and commodified by women and men and the social systems and constraints within which they act and interact. Questions addressed by the authors are framed in terms of current gender theory and the impact of social structures. The resiliency and agency of women are demonstrated by a group of international scholars through the comparison and analysis of empirical data from several countries including the UK, USA, Canada, Taiwan, Indonesia, Iran, the Netherlands, Italy, Spain and the People's Republic of China.